STEM EDUCATION AND THE GENDER GAP: STRATEGIES FOR ENCOURAGING GIRLS TO PURSUE STEM CAREERS - Warsito Warsito; Nur Choiro Siregar; aris gumilar; Roslinda Rosli (Prima: Jurnal Pendidikan Matematika, 2023)
Science, Technology, Engineering, and Mathematics (STEM) are becoming increasingly important in today's society as they drive innovation and shape the future of the global economy. However, there is a persistent gender gap in STEM education and careers, with women significantly underrepresented in these fields. This gender gap can be attributed to various factors, including societal stereotypes, a lack of role models, and inadequate support systems for girls and women interested in pursuing STEM careers. This study aims to understand why women tend to avoid STEM careers and how to encourage women to be more involved in STEM fields. This study uses qualitative methods with interview collection techniques. The results of the study show that there are several aspects for women to be involved in STEM (1) initial exposure to the STEM field, (2) providing positive role models for women, (3) creating an inclusive and supportive learning environment, and (4) working actively to eliminate gender bias and stereotypes. Encouraging girls and young women to pursue STEM fields is critical as it not only helps create a more diverse and inclusive workforce but also opens up opportunities for innovation and advancement. Studies have shown that exposing girls to STEM fields at an early age can significantly impact their interest and confidence. In addition, they have access to positive female role models. They are creating an inclusive and supportive learning environment for girls in STEM fields. In conclusion, addressing the STEM gender gap and encouraging girls to pursue STEM careers is critical to creating a diverse and inclusive workforce, driving innovation and progress.